Synthesis and Physico-Chemical Characterization and Biological Activity of Fe(II) and Zn(II) Complexes of Rabeprazole - Malik, Suman; Das, Supriya; Jain, Bharti (Asian Journal of Chemistry, 2010)
The template condensation between rabeprazole drug which is 2-([4-(3-methoxypropoxy)-3- methylpyridin-2-yl]methylsulfinyl)-1H- benzimidazole] and ferrous(II) sulphate and Zn(II) chloride in 1:2 ratio is described. Formation of new complex [(C18H21N3O3S)2Fe·2H2O] and [(C18H21N3O3S)2Zn] have been supported by elemental analysis, conductivity measurements and spectral studies including IR, 1H NMR, UV and SEM studies. The molar conductance measurements of the complex in DMSO indicate that the complex is non-electrolytic in nature. The spectroscopic results show the involvement of C=N and S=O groups in coordination to the central metal ion. The magnetic moment value of ferrous(II) complex is 5.83 BM suggesting a high spin state of the metal ion in this complex. Based on spectral studies, octahedral geometry has been proposed for the Fe(II)complex and tetrahedral geometry for Zn(II)complex. The ligand and its complexes were tested for their antibacterial and antifungal activities against bacteria Pseudomonas, Staphylococcus aureus and fungi Aspergillus niger. It is observed that the complexes are better bactericidal agent than the parent drug.